54.4k views
4 votes
EVAN

Enter the value of n so that the expression (-2y-3) + (-6y-5) is equivalent to (ny --8),
t
t
1
2
3
4
5
6
7.
8
9
0

EVAN Enter the value of n so that the expression (-2y-3) + (-6y-5) is equivalent to-example-1

1 Answer

2 votes

Answer:

n = -8

Explanation:

Given the expression

(-2y-3) + (-6y-5) = (ny -8),

Expanding the LHS

-2y-3 - 6y -5 = ny - 8

-2y-6y-3-5 = ny - 8

-8y - 8 = ny - 8

Compare both sides

-8y = ny

-8 = n

Swap

n = -8

Hence the value of n is -8

User Ennuikiller
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.